Entrepreneurship Education Content and Venture Creation Potential Among Colleges Of Education Graduates In Kano State Nigeria - Nana, Rabi'u Aminu; Muhammad, Kibuuka (NIU Journal of Humanities, 2018)
The study examined the relationship between entrepreneurship education content and venture creation potentials among graduates of College of Education in Kano state Nigeria. The design was descriptive and involved 385 graduates randomly selected from three Colleges of Education. Data were collected using a researcher made questionnaire. Descriptive statistics, Pearson’s linear correlation and linear regression were used to analyze data. The findings revealed a positive significant relationship between entrepreneurship education content and venture creation potentials among graduates of Colleges of Education in Kano state Nigeria (F = 24.868, Sig. = 0.000), hence rejecting the null hypothesis. This led to the conclusion that entrepreneurship education content has a strong positive relationship with venture creation potentials among graduates of Colleges of Education in Kano state Nigeria. It is recommended that government and other stakeholders should establish standard entrepreneurship education centers, where students can put the content learned in classrooms into practice. This adds more weight in developing their interest towards venture creation as a means for self-employment.